Exploring disorder correlations in superconducting systems: spectroscopic insights and matrix element effects - Neverov, Vyacheslav D.; Lukyanov, Alexander E.; Krasavin, Andrey V.; Vagov, Alexei; Lvov, Boris G.; Croitoru, Mihail D. (Beilstein Journal of Nanotechnology, 2024)
Understanding the intricate interplay between disorder and superconductivity has become a key area of research in condensed matter physics, with profound implications for materials science. Recent studies have shown that spatial correlations of disorder potential can improve superconductivity, prompting a re-evaluation of some theoretical models. This paper explores the influence of disorder correlations on the fundamental properties of superconducting systems, going beyond the traditional assumption of spatially uncorrelated disorder. In particular, we investigate the influence of disorder correlations on key spectroscopic superconductor properties, including the density of states, as well as on the matrix elements of the superconducting coupling constant and their impact on the localization length. Our findings offer valuable insights into the role of disorder correlations in shaping the behavior of superconducting materials.
Keywords: disorder; spatial correlations; superconductivity